2021
DOI: 10.1186/s12913-021-06750-4
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of English language proficiency on healthcare access, use, and outcomes among immigrants: a qualitative study

Abstract: Background Immigrants from culturally, ethnically, and linguistically diverse countries face many challenges during the resettlement phase, which influence their access to healthcare services and health outcomes. The “Healthy Immigrant Effect” or the health advantage that immigrants arrive with is observed to deteriorate with increased length of stay in the host country. Methods An exploratory qualitative design, following a community-based researc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 54 publications
1
63
0
Order By: Relevance
“…Language proficiency can have an impact on the way patients with language barriers report their symptoms to their family members who might act as interpreters. This situation can be confusing for health-care providers; these findings are similar to those of several other studies [ 26 , 37 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Language proficiency can have an impact on the way patients with language barriers report their symptoms to their family members who might act as interpreters. This situation can be confusing for health-care providers; these findings are similar to those of several other studies [ 26 , 37 ].…”
Section: Discussionsupporting
confidence: 89%
“…Until now, how a patient’s cultural, communicational, and religious characteristics interact with their utilization of a health-care service has not been well investigated [ 21 ]. Moreover, linguistic issues are important because they accentuate and amplify other cultural barriers, such as values, norms, and gender-related issues, through a feeling of miscommunication and exclusion [ 22 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this study did not intentionally focus on migrants, the majority of the non-English preference participants were migrants in the UK. Higher English language proficiency may determine access to better health care services and information among migrants, which could consequently lead to exposure to healthy lifestyles and protective factors against adverse health conditions [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in Montreal and Paris, documents were available in many different languages, whereas in Bamako and Recife documents were only available in one language. While the need for information in a variety of languages varies based on the linguistic profiles of countries, studies have shown that reducing language barriers is related to a better understanding of instructions and is also linked to improved health outcomes [25].…”
Section: Discussionmentioning
confidence: 99%